Moby Dick; Or, The Whale - Melville, Herman, 1819-1891 (Salt Lake City, UT : Project Gutenberg, 2001)
"Moby Dick; Or, The Whale" by Herman Melville is an epic novel published in 1851. Sailor Ishmael narrates the obsessive quest of Captain Ahab, who commands the whaling ship Pequod in pursuit of Moby Dick, a giant white sperm whale that destroyed his leg. Ahab's vengeful mission drives the ship and its diverse crew across the world's oceans, blending realistic whaling details with profound explorations of fate, good and evil, and human obsession against nature's raw power. (This is an automatically generated summary.)
Wikipedia page about this book: https://en.wikipedia.org/wiki/Moby-Dick
Project Gutenberg eBook #15 is believed to have the highest quality of the three editions of this eBook in the Project Gutenberg collection. #2701 and #2489 are the others. In addition, there is a computer-generated audio eBook, #9147, and a human audio performance, #28794.
Release date is 2001-01-01
Keywords: Whaling -- Fiction; Sea stories; Psychological fiction; Ship captains -- Fiction; Adventure stories; Mentally ill -- Fiction; Ahab, Captain (Fictitious character) -- Fiction; Whales -- Fiction; Whaling ships -- Fiction